Development and Validation of RP-HPLC-PDA Method for Simultaneous Estimation of Baclofenand Tizanidine in Bulk and Dosage Forms - Buchi N. Nalluri, K. Sushmitha, B. Sunandana, D. Prasad Babu (Journal of Applied Pharmaceutical Science)
A simple, specific, and accurate reverse phase liquid chromatographic method was developed for the estimation of Tizanidine (TZN) and Baclofen (BCF) in combination. A Phenomenex -C18 (150×4.60 mm Dimensions, 5μm Particle size) column with mobile phase containing methanol: water (53:47) was used at isocratic mode and eluents were monitored at228 nm. The retention times of TZN and BCF were 2.03 and 4.1min respectively and both the drugs showed good linearity in the concentration range of 10-50 μg/mL with a correlation coefficient (R) of 0.9992 and 0.9993 respectively. The proposed method was validated as per ICH guidelines and method showed good precision with percent relative standard deviation less than 2%. The percentage assay values of TZN and BCF were found to be 99.72 and 98.56respectively and recovery values are within the limits of 98-102% indicating the proposed method was accurate and precise for the simultaneous estimation of TZN and BCF in bulk and pharmaceutical dosage forms.
Keywords: Simultaneous estimation,Reverse phase liquid chromatography,Validation.